Impact Analysis of Green Microfinance, Government Regulation, and Environmental Credit Innovation on MSME Productivity in Yogyakarta - Lesmana, Tera; Lasmiatun, KMT; Arini, Rani Eka (Westscience Press, 2025)
This study investigates the impact of Environmental Credit Innovation, Government Regulation, and Green Microfinance on the productivity of Micro, Small, and Medium Enterprises (MSMEs) in Yogyakarta, Indonesia. Using data from 140 MSMEs, the research employs Structural Equation Modeling with Partial Least Squares (SEM-PLS 3) to analyze the relationships between these factors. The results show that all three variables—Environmental Credit Innovation, Government Regulation, and Green Microfinance—positively influence MSME productivity. Specifically, Environmental Credit Innovation, Government Regulation, and Green Microfinance significantly contribute to improving MSME performance. The model explains 71.3% of the variance in MSME productivity, indicating substantial explanatory power. Additionally, the predictive relevance of the model highlights its practical utility for policy recommendations. The findings suggest that fostering environmentally responsible practices, simplifying regulatory processes, and expanding access to green finance are key drivers for boosting MSME productivity in the region.